2021
DOI: 10.1136/bcr-2021-242853
|View full text |Cite
|
Sign up to set email alerts
|

Acute icteric hepatitis as the first isolated symptom of COVID-19

Abstract: Patients with COVID-19 may be asymptomatic or present with extrarespiratory symptoms, such as liver injury. It has been reported that 22.5%–46.2% of patients have moderate elevation of liver enzymes. To our knowledge, acute hepatitis has never been described as an isolated symptom of COVID-19 in a previously healthy patient. We report the case of a 53-year-old patient with COVID-19 whose first clinical presentation was acute icteric hepatitis, several days before the development of others symptoms. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several reports have highlighted the occurrence of liver enzyme abnormalities, acute hepatitis, and an ALF associated with SARS-CoV-2 infection [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. It has been documented that approximately 76.3% to 82.5% of COVID-19 cases display abnormal liver test results [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports have highlighted the occurrence of liver enzyme abnormalities, acute hepatitis, and an ALF associated with SARS-CoV-2 infection [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. It has been documented that approximately 76.3% to 82.5% of COVID-19 cases display abnormal liver test results [ 35 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have highlighted the occurrence of liver enzyme abnormalities, acute hepatitis, and an ALF associated with SARS-CoV-2 infection [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. It has been documented that approximately 76.3% to 82.5% of COVID-19 cases display abnormal liver test results [ 35 , 37 ]. Medetalibeyoglu et al further demonstrated that elevated levels of AST and ALT, along with an AST/ALT ratio greater than 1, indicated a more severe disease course and increased mortality in COVID-19 patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation